Developing and Validating an Effective Pediatric and Adolescent HIV Testing Eligibility Screening Tool for High-Volume Entry Points in Uganda. (1st November 2021) - Katureebe, Cordelia; Ashburn, Kim; Machekano, Rhoderick; Gill, Michelle M.; Gross, Jessica; Kazooba, Patrick; Kiyonga, Angehulha; Taasi, Geoffrey; Adler, Michelle; Nazziwa, Esther; Rivadeneira, Emilia D.; Kekitiinwa, Adeodata; et al.
Abstract : Introduction: Because of low pediatric HIV prevalence, more tests are needed to find 1 HIV-positive child compared with adults. In Uganda, the number needed to test (NNT) to find 1 new HIV-positive child was 64 in outpatient departments (OPDs) and 31 through index testing. We aimed to develop and validate a pediatric (1.5–14 years) screening tool to optimize testing approaches. Methods: Phase 1 evaluated the performance of 10 screening questions in 14 OPDs using a variable selection algorithm to evaluate combinations of screening questions. Using logistic regression, we identified the number of screening questions with the best predictive accuracy using the receiver operation characteristic curve. Phase 2 validated the proposed tool in 15 OPDs and 7 orphan and vulnerable children programs. We estimated sensitivity, specificity, and NNT accounting for intercluster correlations. Results: A total of 3482 children were enrolled. The optimal model included reported HIV-positive maternal status or 2/5 symptoms (sickly in the last 3 months, recurring skin problems, weight loss, not growing well, and history of tuberculosis). The proposed tool had sensitivity of 83.6% [95% confidence interval (CI): 68.1 to 92.4] and specificity of 62.5% (95% CI: 55.0 to 69.4). The tool was validated in a sample of 11, 342 children; sensitivity was 87.8% (95% CI: 80.9 to 92.5) and specificity 62.6% (95% CI: 54.8 to 69.7) across OPDs and community sites. In OPDs, sensitivity was 88.1% (95% CI: 80.8 to 92.8) and specificity 69.0% (95% CI: 61.9 to 75.3). The NNT was 43 (95% CI: 28 to 67) across settings and 28 (95% CI: 20 to 38) for OPD. Conclusions: This HIV screening tool has high sensitivity and reasonable specificity, increasing testing efficiency and yield for children and adolescents. Abstract : Supplemental Digital Content is Available in the Text.